Hukum Kewarisan Islam dalam Konstruksi Teori Qath’i dan Zanni: Islamic Inheritance Law in Theory Construction of Qath'i and Zanni - Nasrullah, Nasrullah (Mitsaqan Ghalizan, 2023)
In ushul Fiqh the terms qath'i and zhanni are used to describe the sources of Islamic legal texts, both the Qur'an and hadith in two ways namely al-tsubut (existence) or al-wurud (sourced from truth) and al-dalalah (interpretation). In terms of qath'i, zhanni al-tsubut and al-wurud the scholars agree that the Qur'an and mutawatir hadiths are qath'i, while the hadith ahad is zhanni al-tsubut. They differed from al-Dalah in terms of qath'i and zhanni (interpretation). According to the expert scholar Ushl Fiqh, if a religious text (verse of the Qur'an or Hadith) contains only one clear meaning and does not allow room for other interpretations, and mentions certain numbers, then the text is considered qath'i al- dalah. This qath'i al-dalalah category contains religious texts on inheritance law. Whereas contemporary scholars state that qath'i and zhanni al-dalalah in the Qur'an and hadith cannot be seen from the clarity of the meaning of the pronunciation, they can be seen from the desired essence of the pronunciation, which is commonly known as maqasid al-shariah. The maqasid approach must be added to the theory of ta'abbudi and ta'aqquli.